2017
DOI: 10.1177/2055217316688930
|View full text |Cite
|
Sign up to set email alerts
|

Finger and foot tapping as alternative outcomes of upper and lower extremity function in multiple sclerosis

Abstract: BackgroundWhile magnetic resonance imaging contrast-enhancing lesions represent an excellent screening tool for disease-modifying treatments in relapsing–remitting multiple sclerosis (RRMS), this biomarker is insensitive for testing therapies against compartmentalized inflammation in progressive multiple sclerosis (MS). Therefore, alternative sensitive outcomes are needed. Using machine learning, clinician-acquired disability scales can be combined with timed measures of neurological functions such as walking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 12 publications
3
28
0
Order By: Relevance
“…The tapping test goal was similar to previously validated non-smartphone administered tapping tests ( 9 ), where users had to tap as quickly as possible over a 10 s duration and the final score is the average of two attempts. The test uses touch recognition over a rectangular area covering the bottom half of a vertically oriented phone screen (Figure 1A ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tapping test goal was similar to previously validated non-smartphone administered tapping tests ( 9 ), where users had to tap as quickly as possible over a 10 s duration and the final score is the average of two attempts. The test uses touch recognition over a rectangular area covering the bottom half of a vertically oriented phone screen (Figure 1A ).…”
Section: Methodsmentioning
confidence: 99%
“…Measuring neurological functions by patients via smartphones ( 6 8 ) may pose a solution for all aforementioned problems, while additionally empowering patients for greater participation in their neurological care. We have previously found comparable sensitivity and specificity of simple, smartphone-amenable measurements of finger and foot taps to 9HPT and 25FW, respectively ( 9 ). In this study, we explored iterative development/optimization of smartphone-based measurements of neurological functions by: 1.…”
Section: Introductionmentioning
confidence: 91%
“…17 In a study conducted by Tanigawa et al, in which patients with RRMS and patients with progressive MS were compared, the comparison of patients treated for two years and those untreated showed that fine motor skills and walking functions were better in the treated group. 18 In a study by Ontaneda et al, 9-HPT was used to measure the efficacy of fingolimod and rituximab, and significant improvements were observed. 19 Since MS is a progressive disease, as disability increases during the course of the disease, upper and lower extremity functions and work capacity decrease.…”
Section: Discussionmentioning
confidence: 99%
“…Upper extremity capacity tests are used in MS patients to measure both clinical progression and patients' responses to rehabilitation types. Ninehole pegs are the most commonly used tests in the evaluation of upper extremity functions in MS patients in clinical trials (31)(32)(33). EDSS testing, which is insufficient to show disease progression, is supported by additional tests in studies.…”
Section: Minnesota Manual Dexterity Testmentioning
confidence: 99%